Destination Management in Chile: Objectives, Actions and Actors. (6th September 2016) - Pearce, Douglas; Guala, Cesar; Veloso, Katerina; Llano, Sandrino; Negrete, Jorge; Rovira, Adriano; Gale, Trace; Reis, Anabel
Abstract: This paper addresses questions related to the multiple objectives, actions and actors in destination management in Chile. The relationships between these variables in Valparaíso, Los Ríos and Aysén are analysed through a series of matrices, which draw on information contained in tourism and territorial plans and strategies. The current approach emphasizes supply‐side development by many actors and multiple actions. The pattern running throughout the multiplicity of objectives, actions and actors and summarized in a model is that of a common core with complementary variations and a series of main and secondary linkages. The implications of this pattern are then discussed. Copyright © 2016 John Wiley & Sons, Ltd.